Carbon and Nitrogen Isotope Ratios of Food and Beverage in Brazil - Martinelli, Luiz A. (Molecules, 2020)
Several previous studies on targeted food items using carbon and nitrogen stable isotope ratios in Brazil have revealed that many of the items investigated are adulterated; mislabeled or even fraud. Here, we present the first Brazilian isotopic baseline assessment that can be used not only in future forensic cases involving food authenticity, but also in human forensic anthropology studies. The δ(13)C and δ(15)N were determined in 1245 food items and 374 beverages; most of them made in Brazil. The average δ(13)C and δ(15)N of C(3) plants were −26.7 ± 1.5‰, and 3.9 ± 3.9‰, respectively, while the average δ(13)C and δ(15)N of C(4) plants were −11.5 ± 0.8‰ and 4.6 ± 2.6‰, respectively. The δ(13)C and δ(15)N of plant-based processed foods were −21.8 ± 4.8‰ and 3.9 ± 2.7‰, respectively. The average δ(13)C and δ(15)N of meat, including beef, poultry, pork and lamb were -16.6 ± 4.7‰, and 5.2 ± 2.6‰, respectively, while the δ(13)C and δ(15)N of animal-based processed foods were −17.9 ± 3.3‰ and 3.3 ± 3.5‰, respectively. The average δ(13)C of beverages, including beer and wine was −22.5 ± 3.1‰. We verified that C-C(4) constitutes a large proportion of fresh meat, dairy products, as well as animal and plant-based processed foods. The reasons behind this high proportion will be addressed in this study.